Exploring the Hidden Botanical Treasures of Pontal Island: An Urban Forest in the Parque Natural Municipal de Niterói, Rio de Janeiro State, Brazil - Lucas da Cunha Santos; Luiz Fernando Pires Oliveira; André Hoffmann; Adriana Quintella Lobão (Hoehnea)
ABSTRACT The Pontal Island, located in the Parque Natural Municipal de Niterói, stands out as a vital remnant of the Atlantic Forest in Rio de Janeiro. With ecosystems including forest, rocky outcrops, restinga, and mangroves, the island is a biodiversity treasure. This study aimed to conduct a monthly floristic survey from September 2021 to August 2022. The study found 194 species, divided into four plant communities, with Fabaceae, Euphorbiaceae, and Myrtaceae being the most representative families. Five species are endemic, ten are threatened, and twelve are new records for Niterói.